1977
DOI: 10.1002/cne.901710405
|View full text |Cite
|
Sign up to set email alerts
|

The postnatal development of neurons in the dorsal lateral geniculate nucleus of the rat: A Golgi study

Abstract: The postnatal differentiation of neurons in the dorsal lateral geniculate nucleus of the albino rat was studied using the Golgi-Cox technique. At least four animals were used at postnatal ages 12 hours, 2, 4, 6, 8, 10, 11, 12, 13, 14, 15, 16, 18, 20, 24, 28, 35 days and adult. Presumptive thalamo-cortical projection cells (Class A cells of Grossman et al., '73) and non-projection, intrinsic neurons (Class B cells) are distinguishable at 12 hours after birth. At this stage both types of neuron are immature, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(34 citation statements)
references
References 34 publications
5
29
0
Order By: Relevance
“…In contrast as shown in Figure 2 D, soma surface area, although somewhat variable, did not show any significant changes with age. Thus, similar to the observations made in the developing rat dLGN (Parnavelas et al, 1977), relay cells in mouse undergo a rapid growth spurt during early postnatal life. By P7, dendritic branching stabilized and profiles took on a highly stereotypic architecture.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In contrast as shown in Figure 2 D, soma surface area, although somewhat variable, did not show any significant changes with age. Thus, similar to the observations made in the developing rat dLGN (Parnavelas et al, 1977), relay cells in mouse undergo a rapid growth spurt during early postnatal life. By P7, dendritic branching stabilized and profiles took on a highly stereotypic architecture.…”
Section: Resultssupporting
confidence: 85%
“…1). Representative examples are shown in Figure 2 A. Relay cells had type I or class A morphology (Parnavelas et al, 1977) that consists of a thick unbranched axon, relatively large round somata, and multipolar dendritic arbors comprising six to seven primary dendrites. In fact, even cells at early postnatal ages had fairly large somata and complex dendritic trees with a distinct architecture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The light microscopical features of diaphorase-reactive neurons in the rat dLGN (i.e., somatic size and shape, and the morphology and orientation of processes) were similar to the morphological characteristics of class B neurons described in Golgi impregnation studies of the rat dLGN (Grossman et al, 1973;Brauer and Schober, 1973;Kreibel, 1975;Parnavelas et al, 1977;Webster and Rowe, 1984;Gabbott et al, 1986a). We have therefore categorised the diaphorase-reactive neurons as belonging to this class of dLGN neuron.…”
Section: Diaphorase-reactive Neurons In the Dlgnsupporting
confidence: 69%
“…According to Daniels, Pettigrew and Norman (1978) surround inhibition was not detected in the LGN neurons of neonatal kittens, but in kittens older than 3 weeks. Histological studies have shown that intrinsic neurons are already distinguishable in the LGN of newborn kittens and rats (Tombol 1966/7;Morest 1969;Parnavelas et al 1977) and that the density of synapses in the LGN observed in newborn kit tens is about 25% of the adult value (Cragg 1975). These physiological and histological data may well be interpreted as showing that intrageniculate inhibition is already functioning to some extent at birth although it is not organized in such a fashion as to support surround inhibition which is detected only by light stimula tion.…”
Section: Discussionmentioning
confidence: 99%